2021
DOI: 10.1177/23328584211059823
|View full text |Cite
|
Sign up to set email alerts
|

Not All Disadvantages Are Equal: Racial/Ethnic Minority Students Have Largest Disadvantage Among Demographic Groups in Both STEM and Non-STEM GPA

Abstract: An analysis of institutional data to understand the outcome of obstacles faced by students from historically disadvantaged backgrounds is important in order to work toward promoting equity and inclusion. We use 10 years of institutional data at a large public research university to investigate the grades earned by students categorized on four demographic characteristics: gender, race/ethnicity, low-income status, and first-generation college student status. We find that on average across all years of study, un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 59 publications
(89 reference statements)
2
22
0
Order By: Relevance
“…Diversity in STEM is unrepresentative of the diversity in the general population. A 2017 survey by the United States’ National Science Foundation (NSF) found that women, Black, Indigenous, and People of Color (BIPOC), and individuals with disabilities are underrepresented in the STEM workforce relative to the proportions of these groups within the general population . In Canada, Aboriginal students are poorly represented in STEM relative to the general population .…”
Section: Introductionmentioning
confidence: 99%
“…Diversity in STEM is unrepresentative of the diversity in the general population. A 2017 survey by the United States’ National Science Foundation (NSF) found that women, Black, Indigenous, and People of Color (BIPOC), and individuals with disabilities are underrepresented in the STEM workforce relative to the proportions of these groups within the general population . In Canada, Aboriginal students are poorly represented in STEM relative to the general population .…”
Section: Introductionmentioning
confidence: 99%
“…These metrics have been found to benefit groups already overrepresented in higher education. For example, prior work has shown students from groups underrepresented in higher education (e.g., first generation, low income, Black, Latinx, Native) suffered a grade penalty relative to their more privileged peers with students from minoritized racial groups suffering the largest penalties [11]. Other work has shown that the General and Physics GREs are biased against women and students from minoritized racial and ethnic groups [2,12] as well as against students from smaller or less prestigious universities [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to 10 years of institutional data from a large public U.S.-based university (see Figure 2), STEM majors had higher exit rates at 38% for all students with an even higher rate of 65% for underrepresented minority (URM) students, which has been attributed to the student experience in STEM majors (Haak, 2011;Palmer et al, 2011;Tinto, 2017;Whitcomb et al, 2021). Xu (2018) emphasized that institutional conditions and the gap in student support, particularly the quality of the academic program and faculty teaching and accessibility, have dominated the STEM students' college experience and their persistence in academic majors and to graduation.…”
Section: Figurementioning
confidence: 99%
“…Implementation of a CRE curriculum connects the URG student to the topic and increases the student's confidence in the topic through emotional connection, both of which contribute to the student's persistence in STEM (Gorski, 2016). Challenges to the CRE implementation in I-STEM have included a lack of prep time to develop new curricular content, institutional grading policies, and limited time to cover the materials necessary for completing the course (Bowen & Cooper, 2021;Whitcomb et al, 2021). Faculty may push back as they may perceive limits to their academic freedom or that such modifications in instruction may not align with their teaching philosophy (McGee & Bentley, 2017).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation